State-of-the-art review on multi-criteria decision-making in the transport sector - George Yannis; Angeliki Kopsacheili; Anastasios Dragomanovits; Virginia Petraki (Journal of Traffic and Transportation Engineering (English ed. Online), 2020)
Consistent decision-making requires a structured and systematic evaluation of advantages and disadvantages of different choice possibilities. For transport projects, policies or policy measures, and transport options evaluation, various multi-criteria methods have been developed and effectively applied to complement conventional cost effectiveness and cost benefit analysis. The present paper aims to present a state-of-the-art review of pertinent literature regarding multi-criteria decision-making (MCDM) in the transport sector, focusing on the basic concepts and procedure for multi-criteria decision-making in the transport sector, along with its role and evaluation parameters. A large selection of over 50 papers and publications between 1982 and 2019 have been reviewed, in order to provide an insight into the uses of MCDM methods in transport applications. Most commonly used MCDM methods techniques are identified and discussed through a wide review of pertinent literature, research and case studies, leading to interesting conclusions that provide a valuable insight into the use of multi-criteria analysis techniques in transport sector related decision-making. Based on the wide range of reviewed literature, it is concluded that MCDM methods are being applied mostly to evaluate transport options rather than transport policies or projects and the most commonly used MCDM method in transport sector problems are analytic hierarchy process (AHP).